Effectiveness of Deep Learning Basic Physics 1 Using A Multi-Representation Approach Based on Youtube Vidio With Infographic Results - Malik, Fitroh Abdul; Nurfauziah, Rayya; Pratama, Siti Sofiah Tiska; Nurhayati, Tita; Hartini, Tri Isti; Anghel, Cornelia Victoria (Islamic Journal of Integrated Science Education (IJISE), 2025)
The aim of this research is to create infographics based on YouTube videos and evaluate the effectiveness of basic Physics 1 lectures using the multiple representation (MR) approach as a deeper learning process for Uhamka physics education students. A multi-representation (MR) approach that uses representations such as verbal, images, graphics, mathematics and videos can help students gain mastery of Basic Physics 1 concepts, enhancing deeper learning by providing diverse and interactive teaching materials.  Infographics and YouTube videos as learning media for Basic Physics 1 provide a clear and interesting visual picture, making it easier for students to master theoretical physics concepts and relate them to applications in the real world. The results of this research are in the form of infographics which show that students are able to convey the results of basic physics 1 learning via YouTube as an in-depth learning medium using a multi-representation (MR).